1997
DOI: 10.1007/bf00803752
|View full text |Cite
|
Sign up to set email alerts
|

Negative metabolic effects of cyclic GMP are altered in renal hypertension induced cardiac hypertrophy

Abstract: We tested the hypothesis that increasing myocardial cyclic GMP levels would reduce myocardial O2 consumption and that renal hypertension (One Kidney-One Clip, 1K1C)-induced cardiac hypertrophy would change this relationship. Four groups of anesthetized open-chest New Zealand white rabbits (N = 26) were utilized. Either vehicle or 3-morpholinosydnonimine (SIN-1) (10(-4) M, a guanylate cyclase activator) was topically applied to the left ventricular surface of control or 1K1C rabbits. Coronary blood flow (radioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 25 publications
0
21
2
Order By: Relevance
“…The basal myocardial level of cyclic GMP has been reported to be elevated in some types of pressure-load hypertrophy [20,23]. In this and a previous study [22], basal cyclic GMP levels were not shown to be significantly elevated in the renal hypertensive induced hypertrophied rabbits. This has also been demonstrated previously in hypertrophied hearts from T 4 -treated rabbits [31].…”
Section: Discussioncontrasting
confidence: 39%
See 4 more Smart Citations
“…The basal myocardial level of cyclic GMP has been reported to be elevated in some types of pressure-load hypertrophy [20,23]. In this and a previous study [22], basal cyclic GMP levels were not shown to be significantly elevated in the renal hypertensive induced hypertrophied rabbits. This has also been demonstrated previously in hypertrophied hearts from T 4 -treated rabbits [31].…”
Section: Discussioncontrasting
confidence: 39%
“…Previous studies from our laboratory provide further evidence that raising myocardial cyclic GMP by various means lowers O 2 consumption in both control and in renal hypertensive rabbit hearts [22,30]. In this study, we examined whether reducing cyclic GMP degradation through inhibition of the cyclic GMP phosphodiesterase would have differential negative metabolic effects in normal and hypertrophic hearts.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations